EDITORIAL - Sayyid M. Syeed (American Journal of Islam and Society, 1993)
With this fourth issue of 1993, we have completed ten years of publishing the American Journal of Islamic Social Sciences (MISS). We started our journey in 1984 with two issues published during the year under the title of American Journal of Islamic Studies. The next year it was transformed into the American Journal of Islamic Social Sciences (AJISS). The first decade has been quite a pioneering experience, and by now we have been able to identify a growing pool of thinkers, writers, and social scientists who are participating in our endeavor to promote a scholarly forum on Islam. In this issue, Rosalind W. Gwynne's paper is part of a continuing discussion on sunnah. She demonstrates that, in Islamic texts, sunnah does not refer only to the Sunnah of the Prophet, of the local community, or of the Companions and the early community; it can refer to the "Sunnat All&" (the practice of God). She reviews the occurrence of the word sunnah in the Qur'an and, by analyzing some tafair and early documents, shows that it also refers to the universal and unchanghg rules that Allah has established and set into motion. She quotes Wensinck's Concordance of Hadith, in which sunnah has been used in the context of "Sunnat Alliih alongside with "Sunnat a1 Nabi" and sunnah in other senses. Social scientists must concentrate on the "Sunnat AllW in order to understand the universal laws of Allah that govern social phenomena. Louay Safi provides a methodological approach that recognizes revelation as a primary source of knowledge and seeks to use both text and action analysis techniques as necessary theory-building tools. He argues that scientific activity presupposes metaphysical knowledge and that, furthermore, it is even impossible without transcendental ptesuppositions. He also contends that revelation's truth is rooted in empirical reality and that the quality of evidence supporting revealed truth is of no less caliber than that justifying empirical truth. Ebtihaj Al-A'ali presented her paper on "Assumptions Concerning the Social Sciences: A Comparative Perspective" at a recent Toronto, Canada, confemce dealing with cross-cultural knowledge. She summarizes briefly ...